2014
DOI: 10.1200/jco.2013.55.0095
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant, Granisetron, and Dexamethasone for Prevention of Chemotherapy-Induced Nausea and Vomiting After High-Dose Melphalan in Autologous Transplantation for Multiple Myeloma: Results of a Randomized, Placebo-Controlled Phase III Trial

Abstract: The addition of aprepitant resulted in significantly less CINV and had a positive effect on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…The incidence of vomiting on POD1 was significantly less in all patients receiving aprepitant in different doses. However, although most chemotherapy-related antiemetic regimes used 125 mg oral aprepitant,20 there are no dose recommendations for the perioperative use of aprepitant. Most PONV-related trials have used oral doses ranging from 40 to 125 mg without major adverse effects, except for one study which reported dizziness with 125 mg in comparison with 80 mg 15.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of vomiting on POD1 was significantly less in all patients receiving aprepitant in different doses. However, although most chemotherapy-related antiemetic regimes used 125 mg oral aprepitant,20 there are no dose recommendations for the perioperative use of aprepitant. Most PONV-related trials have used oral doses ranging from 40 to 125 mg without major adverse effects, except for one study which reported dizziness with 125 mg in comparison with 80 mg 15.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][23][24][25][26][27] Recently, a randomized placebo controlled trial demonstrated the superiority of adding aprepitant to granisetron with dexamethasone for patients undergoing autologous HSCT for multiple myeloma. 13 Overall, the existing data supports the use of aprepitant during conditioning for autologous HSCT.…”
Section: Introductionmentioning
confidence: 81%
“…Chemotherapy-induced nausea and vomiting (CINV) development after standard premedication (palonosetron and dexamethasone) and after the addition of aprepitant. genic chemotherapy [24,[33][34][35][36][37][38][39]. Moreover, a single oral dose of aprepitant administered prior to abdominal surgery was found to be effective in the prevention of postoperative nausea and vomiting [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a single oral dose of aprepitant administered prior to abdominal surgery was found to be effective in the prevention of postoperative nausea and vomiting [40]. A number of phase III studies have compared the efficacy of a standard antiemetic regimen (5-HT 3 antagonist and dexamethasone) versus a similar regimen plus aprepitant in patients undergoing highly emetogenic chemotherapy [33,[36][37][38][39], showing a higher percentage of complete responses and an improvement in the complete response rate when aprepitant was added. In addition, differences between the aprepitant-containing and standard regimens seen in the first cycle persisted over multiple cycles, and repeated administration of aprepitant appeared to be well tolerated.…”
Section: Discussionmentioning
confidence: 99%